Chemical composition and fumigant effect of essentialoil of Lippia sidoides Cham. and monoterpenes against Tenebrio molitor (L.) (coleoptera: tenebrionidae) - Lima, Rafaela Karin; Cardoso, Maria das Gracas; Moraes, Jair Campos; Carvalho, Stephan Malfitano [UNESP]; Rodrigues, Vanessa Gregorio; Lima Guimaraes, Luiz Gustavo (Universidade Federal de Lavras (UFLA), 2011)
The chemical composition of Lippia sidoides essential oils obtained by hydrodistillation was characterized and quantified by GC/MS and their insecticidal activity by fumigation test was assayed against Tenebrio molitor. Moreover, the toxicity of monoterpenes carvacrol, 1,8-cineol and thymol were also evaluated when applied alone or in binary (1: 1) or tertiary (1: 1: 1) mixture. The essential oil of L. sidoides has as major constituents carvacrol (31.68%), rho-cymene (19.58%), 1,8-cineole (9.26%) and gamma-terpinene (9.21%), from a 21 compounds identified, being 92.53% of total. Both compounds have insecticidal activity against T. molitor, being the degree of toxicity of carvacrol > 1,8-cineole > L. sidoides essential oil > thymol, and its respectively LC(50) at 24h were 5.53; 5.71; 8.04 and 14.71 mu L/L air. When the different mixture of carvacrol, 1,8-cineole and thymol was assayed against T. molitor, the synergism among them was observed. For the mixture of carvacrol: 1,8-cineole LC(50) was 5.34 mu L/L air; carvacrol: thymol 7.67 mu L/L air; 1,8-cineole: thymol 7.51 mu L/L air and carvacrol: 1,8-cineole: thymol 6.34 mu L/L air. Mainly, the monoterpene thymol had a synergic effect, which increased the toxicity of carvacrol and 1,8-cineole, both in binary mixture like carvacrol: thymol and 1,8-cineole: thymol.
Keywords: Alecrim pepper; Mealworm; Natural compound; Toxicity; Synergism